Predictions in the brain using our past to generate a future - Bar, Moshe (New York ; Oxford : Oxford University Press, 2011)
The perspectives represented in this collection span a spectrum from the cellular underpinnings to the computational principles underlying future-related mental processes, and from systems neuroscience to cognition and emotion. In spite of this diversity, they share some core elements.
"Originating from a theme issue published in Philosophical transactions of the Royal Society B: biological sciences."--T.p.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Consciousness -- Research; Self-consciousness (Awareness); Brain -- Evolution